1988
DOI: 10.1177/030006058801600502
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Dothiepin versus Placebo in the Treatment of Pain in Rheumatoid Arthritis and the Association of Pain with Depression

Abstract: The effectiveness of dothiepin (a tricyclic anti-depressant) at a dose of 75 mg given orally at night was compared with placebo for 4 weeks in alleviating pain in 60 patients with classical or definite active rheumatoid arthritis. Patients were classified as either 'depressed' or 'not depressed'. The week before, during and 2 weeks after the study, 600 mg ibuprofen was given orally three times daily to all patients. Compared with placebo, dothiepin produced a significant reduction in daytime pain by the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…Tricyclic antidepressants have been demonstrated in small trials to be effective at reducing pain in rheumatoid arthritis patients(28-30), but have not achieved widespread use for treatment of that disease, given the development of disease-modifying drugs for that condition; at present there are no available disease-modifying treatments for OA. Three recent meta-analyses of anti-depressant treatment for fibromyalgia have all supported the likelihood of a modest effect on pain with tricyclics(31-33), but duloxetine has demonstrated a significant and repeated effect on tender points and measures of pain in randomized, controlled clinical trials(34, 35).…”
Section: Discussionmentioning
confidence: 99%
“…Tricyclic antidepressants have been demonstrated in small trials to be effective at reducing pain in rheumatoid arthritis patients(28-30), but have not achieved widespread use for treatment of that disease, given the development of disease-modifying drugs for that condition; at present there are no available disease-modifying treatments for OA. Three recent meta-analyses of anti-depressant treatment for fibromyalgia have all supported the likelihood of a modest effect on pain with tricyclics(31-33), but duloxetine has demonstrated a significant and repeated effect on tender points and measures of pain in randomized, controlled clinical trials(34, 35).…”
Section: Discussionmentioning
confidence: 99%
“…Only eight of these 15 trials were considered to meet the minimum standards in terms of methodological quality to demonstrate efficacy (Ash et al, 1999;Bird and Broggini, 2000;Frank et al, 1988;Ganvir et al, 1980;Grace et al, 1985;Koh et al, 1997;Macfarlane et al, 1986;Parker et al, 2003).These studies scored from 13 to 22 on a scale with a maximum of 28 (median quality score: 16.4). In almost all these trials, efficacy in the control of pain and symptoms was independent of the antidepressant effect (with the exception of Parker et al (2003) andSarzi Puttini et al (1988)), which included depressed patients). Thus, amitryptyline, trimipramine, dothiepine and paroxetine may have analgesic effects in patients with RA, and amitryptiline may be effective in reducing symptoms in AS.…”
Section: Osteoarthritis and Inflammatory Rheumatic Diseasesmentioning
confidence: 99%
“…No studies have examined the effects of serotonin norepinephrine reuptake inhibitors (SNRIs) on pain in RA, although some have suggested that tricyclic antidepressants, which exert their effects via serotonin and norepinephrine, are effective (1315). In addition, several studies have examined the role of SNRIs in chronic pain conditions associated with defects in central pain processing (e.g., fibromyalgia) (1619).…”
Section: Introductionmentioning
confidence: 99%